The cardiac amyloidosis clinical pathway implementation: a real world experience. (14th October 2021) - Brons, M; Rutten, F.H; Minnema, M.C; Baas, A.F; Asselbergs, F.W; Oerlemans, M.I.F.J
Abstract: Background/Introduction: Prognosis for patients with cardiac amyloidosis (CA) is determined by disease stage at diagnosis, underlining the importance of timely referral. In 2018, a CA clinical pathway was implemented in an Amyloidosis Expert Center in The Netherlands to increase regional awareness. Purpose: To evaluate the impact of CA clinical pathway implementation. Methods: Patients diagnosed before implementation (2007–2018; T1) were retrospectively compared to the period after clinical pathway implementation (2019–2020; T2). Demographics and disease characteristics were collected from electronic health records. Results: In total, 113 patients were diagnosed, mean age 67.8±8.5 years, 26% female. AL-CA was diagnosed in 62%, ATTR-CA in 38%. The number of CA diagnoses/year increased over time (Figure 1). NYHA class III (45% vs. 24%, p=0.04), CA stage (MAYO/Gillmore stage III or IV; 59% vs. 33%, p=0.03) and delay between symptoms and diagnosis (14.5 vs. 8.4 months, p<0.01) improved considerably between T1 and T2. Reasons for referral changed over time, with increasing awareness for right ventricular hypertrophy (9% vs. 36%) and unexplained HFpEF (22% vs 38%). Conclusion: CA patients were diagnosed earlier with less severe symptoms. Clinical pathway implementation facilitated regional increased awareness and improved timely referral. Funding Acknowledgement: Type of funding sources: None.